Negative spin Hall magnetoresistance of normal metal/ferromagnet bilayers - Min-Gu Kang (Nature Portfolio, 2020)
In normal metal/ferromagnet bilayers, the spin Hall magnetoresistance originating from the spin Hall effect of normal metal possesses positive sign regardless of the sign of spin Hall conductivity of normal metal. Here, the authors report negative spin Hall magnetoresistance of Ta/NiFe bilayers due to interfacial spin orbit coupling at interfaces.